Students’ Perception on the Use of English Through Guessing Games in the Classroom - ELISDAWATI, YUNI (ASIAN PUBLISHER, 2023)
The aim of this research is to find out the students’ perception on the use of English through guessing game in the classroom. Klippel stated that the basic rule of guessing games is eminently simple; one person knows something that another one wants to find out. If an English teacher interest to apply guessing games in teaching learning process in the classroom, she/he needs to know about student’s perception to make sure the strategy that applied is beneficial or not for students. If most of students like to apply guessing games in teaching learning process in the classroom, they will effort to get achievement such as can improve their abilities in English, or practice English language in their communication. In this research, the researcher applied a descriptive qualitative method. The population of this research was all students in the first semester of Psychology Islam program study in AcehTamiang Islamic High School. As the sample of this research selected 30 students. The findings of this research showed that the students perception on the use of English through guessing game in the classroom was categorized strong agree based on the interval scale.